The Contagion Effect of Low-Quality Audits - Francis, Jere R.; Michas, Paul N. (The Accounting Review, 2013)
ABSTRACT We investigate if the existence of low-quality audits in an auditor office indicates the presence of a “contagion effect” on the quality of other (concurrent) audits conducted by the office. A low-quality audit is defined as the presence of one or more clients with overstated earnings that were subsequently corrected by a downward restatement. We document that the quality of audited earnings (abnormal accruals) is lower for clients in these office-years (when the misreporting occurred) compared to a control sample of office-years with no restatements. This effect lasts for up to five subsequent years, indicating that audit firms do not immediately rectify the problems that caused contagion. We also find that an office-year with client misreporting is likely to have subsequent (new) client restatements over the next five fiscal years. Overall, the evidence suggests that certain auditor offices have systematic audit-quality problems and that these problems persist over time. Data Availability: All data are publicly available.